Designing an assistive garment for visually impaired with Braille touch / Khairi Asyraf Abdul Karim, Asliza Aris and Rainal Hidayat Wardi - Abdul Karim, Khairi Asyraf; Aris, Asliza; Wardi, Rainal Hidayat (Universiti Teknologi MARA, 2019)
The basis of this project is to create a garment using braille touch specially designed with complete details and a guide to wearing clothes. This study aims to analyze the use of braille on clothing, identify the use of easy-to-wear materials, and overcome the challenges of buying and wearing clothes amongst visually impaired consumers. This study is carried out with methods of interviews focusing on the target age range of 18 - 30 years of the visually impaired people and concentrated in areas of the Federal Territory of Kuala Lumpur. In total, an estimated 5% (1.37 million) are visually impaired and disabled persons, and has a record of 55 persons received the Malaysian Blind Association (MAB) Excellence Achievement Awards 2016/2017. With the assistance provided, this visually impaired community can learn to live independently in their daily activities. This paper is conceptual.